2008
DOI: 10.1186/1465-9921-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of SP-A has a negative impact on the susceptibility of mice to Klebsiella pneumoniae infection after ozone exposure: sex differences

Abstract: Background: Surfactant protein A (SP-A) enhances phagocytosis of bacteria, including Klebsiella pneumoniae, by alveolar macrophages. Ozone, a major air pollutant, can cause oxidation of surfactant and may influence lung immune function. Immune function may also be affected by sex-specific mechanisms. We hypothesized that ablation of SP-A has a negative impact on the susceptibility of mice to Klebsiella pneumoniae infection after ozone exposure, and that sex differences in the effect of ozone do exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
149
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(167 citation statements)
references
References 78 publications
14
149
0
4
Order By: Relevance
“…Particulate matter originated from other sources, such as burning of fossil fuels and biomass, is also associated with increased incidence of pneumonia and increased symptoms and respiratory disease (Souza and Nascimento, 2016). Experimental and epidemiologic studies have demonstrated that the severity of pneumonia has positive associations with exposure of air pollutants (Harrod et al, 2003;Mikerov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter originated from other sources, such as burning of fossil fuels and biomass, is also associated with increased incidence of pneumonia and increased symptoms and respiratory disease (Souza and Nascimento, 2016). Experimental and epidemiologic studies have demonstrated that the severity of pneumonia has positive associations with exposure of air pollutants (Harrod et al, 2003;Mikerov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Показано, что блокирование функции SP-A путем элимина-ции гена SP-A в генетически модифицированных SP-A (-/-) мы-шах или путем снижения функциональной активности белка SP-A вследствие его окисления озоном повышает чувствитель-ность мышей к экспериментальной пневмонии после ингаляции озона [34]. SP-A (-/-) мыши проявляли повышенную чувстви-тельность к ряду патогенных микроорганизмов, включая группу Streptococcus [35], P aeruginosa [36], H. influenza [27], P carinii [37,38], K. pneumonia [34].…”
Section: терапевтический архив 1 2015unclassified
“…SP-A (-/-) мыши проявляли повышенную чувстви-тельность к ряду патогенных микроорганизмов, включая группу Streptococcus [35], P aeruginosa [36], H. influenza [27], P carinii [37,38], K. pneumonia [34]. SP-D (-/-) мыши более восприимчивы к инфекциям дыхательных путей, вызываемым вирусом гриппа [17], респираторно-синцитиальным вирусом [28].…”
Section: терапевтический архив 1 2015unclassified
“…inflammation, oxidative stress, phagocytosis, and other]. For example, human SP-A variants have been shown to differentially enhance the phagocytic activity of AM [3] and mice that lacked SP-A exhibited a lower phagocytic activity and survival [10].…”
mentioning
confidence: 99%
“…Moreover, the SP-A -/-rescue experiment [1] points to the possibility and feasibility of using SP-A as a therapeutic intervention in lung diseases influenced by innate immunity. Furthermore, based on animal studies [10] where small amounts of SP-A elicited significant differences in the AM proteome, it is possible that the SP-A amount needed may not be high, although, further experimentation will be needed to determine optimal amount and efficacy in the clinical setting.…”
mentioning
confidence: 99%